Financial performance analysis of GSK with a comparison to few of the leading pharmaceutical companies of Bangladesh - Anika, Nusrat Sharmeen (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.